Altitudinal changes in secondary metabolite contents of Hypericum androsaemum and Hypericum polyphyllum. (February 2017) - Cirak, Cuneyt; Radusiene, Jolita; Jakstas, Valdas; Ivanauskas, Liudas; Seyis, Fatih; Yayla, Fatih
Abstract: The genus Hypericum (Hypericaceae) has attracted scientific interest as its members have yielded many bioactive compounds. In the present study we investigated the content of hypericin, pseudohypericin, hyperforin, adhyperforin, chlorogenic acid, neochlorogenic acid, caffeic acid, 2, 4-dihydroxybenzoic acid, 13, II8-biapigenin, hyperoside, isoquercitrin, quercitrin, quercetin, avicularin, rutin, (+)-catechin and (−)-epicatechin in aerial parts of plants from populations of H. androsaemum L. and H. polyphyllum Boiss. & Bal. from Turkey growing at different altitudes. The plant materials were dried and subsequently assayed for chemical content by HPLC. All the tested compounds were detected in both species at varying levels depending upon the altitude the plants were growing, except for hypercins and rutin which did not accumulate in H. androsaemum . It was observed that overall the compounds were more abundant in plants from higher altitudes. The differences in the levels of the compounds could contribute to the ability of the plants to deal with the abiotic stress of lower temperature and higher ultraviolet (UV)-B radiation which would be greater at higher altitudes compared to lower altitudes. Highlights: In this study, H. androsaemum and H. polyphyllum were analyzed for the presence of main Hypericum chemicals for the first time. Results indicate significant altitudinal diversity in chemical content of plants. The present data could be beneficial for phytochemical evaluation of the corresponding species.